Discourse theory of law in times of populism - Marxsen, Christian (European law journal : review of European law in context, 2019)
Jurgen Habermas's discourse theory of law has shaped debates on what we consider to be legitimate law. This contribution will firstly identify the Zeitgeist in which discourse theory emerged. Secondly, it points out the emancipatory potential of law that discourse theory has helped us to understand, both on a domestic and a transnational level. Thirdly, the paper turns to discuss two recent challenges for the discourse theory of law, namely (a) the realities of social power that undermine and contradict its promises, and (b) the rise of populism, which places the core normative assumptions of discourse theory in doubt.